HUBUNGAN PENGETAHUAN DAN MOTIVASI SUAMI AKSEPTOR KB SUNTIK DEPO MEDROKSI PROGESTERONE ASETAT (DMPA) DENGAN KEPATUHAN KUNJUNGAN ULANG DI KLINIK BIDAN N. LUMBANGAOL DESA SIMANGARONSANG KECEMATAN DOLOKSANGGUL TAHUN 2018 - Winta Mariana Batubara; Fransiska Debataraja (Jurnal Ilmiah Kebidanan Imelda, 2021)
Injection contraception is a contraceptive that is injected into the body for a certain period of time, then enters the blood vessels absorbed little by little by the body which is useful to prevent pregnancy. This study was to determine the relationship of knowledge and motivation of the husband of the mother of DMPA KB acceptors with the compliance of the re-visit of the clinic of the simangaronsang village midwife. With this type of research using descriptive cross-sectional design analysis with chi square test and sampling technique using random sampling method with a total sample of 58 respondents with analysis of univariate analysis data and bivariate analysis. The results showed that there was a relationship of knowledge with compliance with repeat visits where df: 2 was obtained obtained X² count (30,644)> X² table (5,591), the husband's motivation was related to repeated visit compliance where df: 2 obtained X² count (13,469)> X² table (5.591), and the source of information is related to the compliance of repeat visits where df: 2 obtained X² count (8.028)> X² table (5.591). It is expected that the respondent will increase the knowledge and motivation of the husband in increasing the respondent's compliance in conducting a repeat visit so as to improve family welfare.